Mortalitas Tuberkulosis Paru di RSUP Prof. dr. I.G.N.G. Ngoerah, Denpasar - I Gede Ketut Sajinadiyasa; Gede Dilajaya Robin; Putu Andrika (PT Dexa Medica, 2026)
Background: Pulmonary tuberculosis (TB) is the second leading cause of death from infectious disease worldwide. According to the World Health Organization (WHO) report in 2022, the global number of deaths due to TB reached 1.3million cases. In Indonesia, the mortality rate due to pulmonary TB in 2021 was 52 cases per 100,000 population. Methods: This is a descriptive study with cross-sectional approach to determine the mortality rate of TB. The subjects were ofpulmonary TB patients recorded at RSUP Prof. dr. I.G.N.G. Ngoerah, Denpasar, in 2023. The sampling technique used was total sampling. Results: Among the 84 subjects, 33 deaths were recorded. Based on sex, death occurred in 8 (9.5%) female subjects and 25 (29.8%) male subjects. Based on age, death occurred in 8 (9.5%) patients aged ≥60 years and 25 (29.8%) patients aged <60 years. Based on HIV status, death occurred in 20 (23.8%) patients with nonreactive HIV status and 13 (15.5%) patients with reactive HIV status. Based on diabetes status, death occurred in 4 (4.8%) diabetic patients and 29 (34.5%) nondiabetic patients. Based on the type of pulmonary TB, death occurred in 13 (15.5%) patients with clinically diagnosed pulmonary TB and 20 (23.8%) patients with bacteriologically confirmed pulmonary TB. Conclusion: Mortality due to pulmonary TB was more commonly observed among males, individuals under 60 years of age, those withnonreactive HIV status, nondiabetes, and those with bacteriologically confirmed pulmonary TB.